GEOPOLITIK INDONESIA - Akmaliza, Anggi; Nehe, Annisa Shakira; Sihotang, Azron Muqsitin; Hakim, Baihaqy; Purmadana, Eka; Praswadi, Hari; Raziq, Maulidin; Paulina, Melda; Darmawan, Mhd. Rendi; Nurdiana; Suhada, Reza; Sabina, Sahnia (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
Geopolitics of Indonesia have been formed since the time of the kingdom of Indonesia that began Sriwijaya and Majapahit. It discusses strategies to Indonesia in maintaining his good- Indonesiaan in social, cultural, geographic, demographic, and Security in accordance with the purpose of the state or the nation's ideals. Therefore, various prerequisites must be met for the achievement of the ideals of the trip was guaranteed, such a precondition is called geo-political, which are briefly formulated in the form of the Wawasan Nusantara. Thus, the role of conception, is in managing natural resources which can be used politically conscious citizenship plus state and nation. State of Indonesia is not just a scientific description but rather a long stake that limit the corridor between the dynamics of our society which is expected in between. When viewed in terms of ideology Pancasila principles are described sila-over descriptions of national ideals and supported by a summary of the core ideas of philosophy and science. The purpose of this paper is to discuss the integration of diversity that exist in Indonesia, let alone be seen from the geographical aspect of Indonesia lies between the two continents of Asia and Australia and two oceans namely the Indian and Pacific oceans are very prone to disintegration. Readings re-geohistoris Globalization and geopolitics have a very important role in regulating the policies put forward in the achievement of National Security of such ideals.